Playing the Original Game Boy Tetris Using a Real Coded Genetic Algorithm - da Silva, Renan Samuel; Stubs Parpinelli, Rafael (2017 Brazilian Conference on Intelligent Systems (BRACIS), 2017)
Tetris is a very popular game, having sold more than 450 millions units according to Forbes and it is also a very popular research subject in the field of Artificial Intelligence and Computational Intelligence. This work has two main goals. The first goal consists of providing a standardized testing scenario based on an Emulator to run the Original Tetris Game. The second goal is to test several feature sets found in the literature in the proposed Real Coded Genetic Algorithm Based Agent. The results obtained showed the viability of having an agent playing the Original Tetris Game.